2008
DOI: 10.1083/jcb.200711032
|View full text |Cite
|
Sign up to set email alerts
|

DDA3 recruits microtubule depolymerase Kif2a to spindle poles and controls spindle dynamics and mitotic chromosome movement

Abstract: Dynamic turnover of the spindle is a driving force for chromosome congression and segregation in mitosis. Through a functional genomic analysis, we identify DDA3 as a previously unknown regulator of spindle dynamics that is essential for mitotic progression. DDA3 depletion results in a high frequency of unaligned chromosomes, a substantial reduction in tension across sister kinetochores at metaphase, and a decrease in the velocity of chromosome segregation at anaphase. DDA3 associates with the mitotic spindle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
103
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(117 citation statements)
references
References 32 publications
(63 reference statements)
14
103
0
Order By: Relevance
“…Although our results showed clear targeting to the 3Ј-UTR of the KIF2A mRNA, transfection with miR-183 resulted in a significant increase in the presence of cells with monopolar spindles only in HeLa cells, but not in HDF or HTM cells. Formation of bipolar spindles has been reported under conditions of partial knockdown of KIF2A in other cell types (9). The difference on the effects of miR-183 on the formation of monopolar spindles observed between HeLa cells and normal HDF and HTM cells are not likely to depend on differences in targeting the 3Ј-UTR of KIF2A because, in all cases, miR-183 induced a similar decrease in expression of both the KIF2A transcript and protein.…”
Section: Discussionmentioning
confidence: 71%
“…Although our results showed clear targeting to the 3Ј-UTR of the KIF2A mRNA, transfection with miR-183 resulted in a significant increase in the presence of cells with monopolar spindles only in HeLa cells, but not in HDF or HTM cells. Formation of bipolar spindles has been reported under conditions of partial knockdown of KIF2A in other cell types (9). The difference on the effects of miR-183 on the formation of monopolar spindles observed between HeLa cells and normal HDF and HTM cells are not likely to depend on differences in targeting the 3Ј-UTR of KIF2A because, in all cases, miR-183 induced a similar decrease in expression of both the KIF2A transcript and protein.…”
Section: Discussionmentioning
confidence: 71%
“…It is interesting to note that no bundling activity of DDA3 is observed in mitotic cells. 2 Thus, it is not clear whether the MT-bundling activity of DDA3 is physiologically relevant to mitosis.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13] We recently showed that DDA3 is a regulator of the mitotic spindle essential for mitotic progression. 2 Depletion of DDA3 results in a high frequency of unaligned chromosomes, a substantial reduction in tension across sister kinetochores at metaphase, and a decrease in the velocity of chromosome segregation at anaphase. DDA3 associates with the mitotic spindle and controls MT dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations